Radiation study on the parallel topology of SiC MOSFET and Si IGBT inverter - Yuxing Dai; Zijie Zheng; Zishun Peng; Wen Hu; Jun Wang; Zhenxing Zhao; Yachao Yang; Yi Yang (Energy Reports, 2023)
The electromagnetic radiation interference mechanism from multiple noise sources on the parallel topology of SiC MOSFET and Si IGBT Inverter is blurred, which will seriously affect the high reliability application of the structure. In order to solve this problem, a topological radiation EMI prediction method is proposed, the method includes the establishment of radiation equivalent models and radiation guidelines, the proposed inverter parallel topology radiation. The modeling method of electromagnetic interference can effectively analyze the influence of radiation interference of SiC and Si devices coupled with each other, and the established PCB radiation near and far field simulation can effectively realize the accurate prediction of radiation interference of inverter parallel topology, and finally the experimental platform of the parallel SiC MOSFET and Si IGBT inverter is built and tested, the test results demonstrate the accuracy of the proposed method.